2021
DOI: 10.21608/ejhm.2021.159674
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasound in the Assessment of Pediatric Non-Traumatic Gastrointestinal Emergencies

Abstract: Background: Non-traumatic gastrointestinal emergencies in the children and neonatal patients and the presenting characteristics ultrasound features on the longitudinal and axial axes are a dilemma for the radiologist in the emergency room. The most frequent emergencies are appendicitis, intussusceptions, hypertrophic pyloric stenosis, and volvulus due to intestinal malrotation. Objectives: this work aimed to assess the role of ultrasound in the assessment of pediatric non-traumatic gastrointestinal emergencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
(14 reference statements)
2
5
0
Order By: Relevance
“…Their study showed that ultrasound is a reliable and efficient screening method that accurately identifies the causes of upper gastrointestinal disease in children [9] . Our results agree with those documented by [8] . In terms of Mesenteric ultrasonographic findings of the studied patients, parallel to our results, Banoub et al showed that Anechoic mesentery represented 5 (2.4%) patients, echogenic represented 12.2% of the patients, hyperechoic represented 90 (43.9%) patients and hypervascularization represented 32 (15.6%) patients [8] .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Their study showed that ultrasound is a reliable and efficient screening method that accurately identifies the causes of upper gastrointestinal disease in children [9] . Our results agree with those documented by [8] . In terms of Mesenteric ultrasonographic findings of the studied patients, parallel to our results, Banoub et al showed that Anechoic mesentery represented 5 (2.4%) patients, echogenic represented 12.2% of the patients, hyperechoic represented 90 (43.9%) patients and hypervascularization represented 32 (15.6%) patients [8] .…”
Section: Discussionsupporting
confidence: 94%
“…Our results agree with those documented by [8] . In terms of Mesenteric ultrasonographic findings of the studied patients, parallel to our results, Banoub et al showed that Anechoic mesentery represented 5 (2.4%) patients, echogenic represented 12.2% of the patients, hyperechoic represented 90 (43.9%) patients and hypervascularization represented 32 (15.6%) patients [8] . Regarding site of pathology of the studied patients, conforming our results, Banoub et al showed that 5 (2.4%) patients had pyloric lesions, 7 (3.4%) patients had duodenum lesions, 5 (2.4%) patients had jejunum lesions, 22 (10.7%) patients had ileum lesions, 53 (25.9%) patients had ileocecal lesions, 9 (4.4%) patients had large intestine lesions and 104 (50.7%) patients had not determined/not GIT lesions.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations